Prenatal diagnosis in a fetuses with a clenched hands, overlapping fingers, and clubfoot due to MED12 deficiency in three affected siblings: A case report - Xue, Huiqin; Tang, Qiaoyin; Feng, Yu; Zhao, Chenyue; Xu, Ke; Gu, Weiyue; Xue, Zhaoyu; Li, Xinyan; Jiang, Jinsong; Lu, Hongyong; Sun, Xiayu; Wu, Jianrui; et al. (Frontiers in Genetics, 2023)
Fetal clenched hand with overlapping fingers is more common in aneuploidy syndromes and was not well-documented in MED12 deficiency. This study reports the clinical and genetic findings of three affected siblings from a Chinese family. Chromosome karyotype analysis diagram show karyotypes of three children were normal. Trio whole-exome sequencing and Sanger sequencing verification found that there was a MED12 R296Q variant in normal mothers and their two offspring. A pattern of clenched hand with overlapping fingers (clinodactyly) and clubfoot were found in all the 3 affected siblings by Three-dimensional ultrasound. The discovery of this case shows that even if the chromosome karyotype is normal, comprehensive prenatal genetic diagnosis is required when the ultrasound results show clenched hand with clinodactyly and clubfoot symptoms.